AL-QUR'AN SEBAGAI PANDUAN KONSERVASI LINGKUNGAN: STUDI ATAS NILAI AMANAH DAN KEPEMIMPINAN MANUSIA TERHADAP ALAM - Muhammad Atsiil Al Ahnaf; Sholahuddin Al Ayubi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
To address the increasingly concerning problem of environmental damage, an approach from various perspectives is needed, including those related to faith and religious beliefs. This study examines how the Qur'an places humans as caliphs (leaders) on earth and has the responsibility to protect and care for the environment. Using the literature study method and the thematic interpretation approach (maudhu'i), the results of the study show that the Qur'an provides a strong normative basis for building good ethics. Unlike the concept of caliph, the value of amanah describes the moral obligation to protect God's creation. The results show that from the perspective of the Qur'an, environmental conservation has goals that are not only ecological but also theological and ethical. Therefore, incorporating Qur'anic principles into discussions and practices of environmental conservation is essential and important to address the challenges faced by world ecology today